A Comparative Study of Total Factor Productivity between China and Japan - YU, XIN (2013)
Since FP growth is the primarily influence factor on the contribution of economic growth. The purpose of this study is to critically distinguish the economic growth between China from 1990 to 2010 and Japan from 1981 2006. Using the State Space Model based on three quantitative methods they are the Solow Residual Approach, Latent Varible Approach and Potential Output Approach to compute and compare TFP rate in two countries. Afterwards, by combining Japan’s economic performance in different periods, we can find that China’s economic growth pattern and future development since 2000 is strikingly similar to Japan prior to 1990, therefore, it can be deduced that China’s future economic development may have a great tendency to bubble foam. Accordingly, some feasibility suggestions are given out for shaping economy policy: to support the real economy, to expand domestic demand to emphasis on personnel training, and macroeconomic policy adjustments.